Statistical Process Control - Amin Mohammed, Mohammed (Cambridge University Press, 2024)
Explores the role of statistical process control in offering an intuitive, practical, and robust approach to supporting efforts to improve healthcare. This title is also available as Open Access on Cambridge Core.